Bioaccumulation as a method of removing psychoactive compounds from wastewater using aquatic plants - Žabka, D; Vojs Staňová, A; Horáková, I; Butor Škulcová, A; Grabic, R; Špalková, V; Gál, M; Mackuľak, T (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2023)
Since WWTPs are not able to eliminate all psychoactive pharmaceuticals, these compounds become a part of the aquatic ecosystem. Our results indicate that compounds such as codeine or citalopram are eliminated with low efficiency (<38%), and compounds such as venlafaxine, oxazepam, or tramadol even with almost no efficiency. Lower elimination efficiency may be caused by the accumulation of these compounds in the wastewater treatment process. This study is focused on the possibility to remove problematic psychoactive compounds using aquatic plants. HPLC-MS analysis of the leaf extract obtained from studied plants showed that the amount of accumulated methamphetamine was highest in Pistia stratiotes and lower in the leaves of Limnophila sessiliflora and Cabomba caroliniana. However, tramadol and venlafaxine were accumulated considerably only in Cabomba caroliniana. Our study demonstrates that especially these three compounds - tramadol, venlafaxine, and methamphetamine, are accumulated in aquatic plants and can be removed from the aquatic environment. In our study was also observed that helophytic aquatic plants show a higher ability to remove psychoactive compounds from wastewater. Iris pseudacorus showed the best results in selected pharmaceuticals removal with no bioaccumulation effect in leaves or roots.
Keywords: Plants; léčivé přípravky; WWTP; Pharmaceutical Preparations; Ecosystem; Environmental Monitoring; Aquatic plants; Bioaccumulation; Psychoactive pharmaceuticals; Tramadol; tramadol; Wastewater; methamfetamin; monitorování životního prostředí; Water Pollutants, Chemical; Venlafaxine Hydrochloride; venlafaxin hydrochlorid; odpadní voda; rostliny; Methamphetamine; chemické látky znečišťující vodu; ekosystém